One-step extraction of highly fluorescent carbon quantum dots by a physical method from carbon black. (9th June 2017) - Han, Bingyan; Yu, Mingbo; Pen, Tingting; Li, Ying; Hu, Xixi; Xiang, Rongchao; Hou, Xufen; He, Gaohong
Abstract : Herein, we introduced a kind of physical method using acetone to directly extract fluorescent carbon quantum dots from ordinary carbon black in one step. Abstract : Herein, we introduced a kind of physical method using acetone to directly extract fluorescent carbon quantum dots (CQDs) from ordinary carbon black in one step. The as-extracted CQDs exhibited an excitation-dependent emission behavior and a high quantum yield of up to 19.01%. Moreover, we find that the polarity of the solvent will affect the size of CQDs for the first time.